The influence of entrepreneurship education, family support, and campus environment on entrepreneurial interest with self-efficacy as an intervening variable - Nadila Febriani; Suhardi Suhardi; Mat Amin (Economic: Journal Economic and Business, 2026)
This study aims to analyze the influence of Entrepreneurship Education, Family Support, and Campus Environment on Entrepreneurial Interest with Self-Efficacy as an intervening variable. The phenomenon of low entrepreneurial interest among college graduates despite various strengthening programs has been implemented is the main background of this study. Using a quantitative approach, data was collected through an online questionnaire from 125 students who have taken entrepreneurship courses. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique using SmartPLS software. The results showed that Entrepreneurship Education and Family Support have a positive and significant effect on Self-Efficacy. However, it was found that the Campus Environment has no significant effect on students' Self-Efficacy or Entrepreneurial Interest. Self-Efficacy proved to be a strong predictor of Entrepreneurial Interest and plays a significant mediator in bridging the influence of education on interest. This finding confirms that strengthening psychological aspects through self-confidence is far more effective than simply providing physical facilities on campus. This study recommends the need for synchronization between the academic curriculum and family emotional support in order to crystallize students' entrepreneurial mentality.